Upaya Meningkatkan Kemampuan Motorik Halus Anak Melalui Kegiatan Mozaik Biji Jagung di TK Islam Al Mansur Dukun Karangtengah Demak - Aqifah, Shinta Zahrotul; Handayani, Dwi Asih Kumala; Rahayu, Sri Setiyo (Journal of Research and Development Early Childhood, 2025)
This study aims to determine (1) Whether corn seed mosaic activities can improve children's fine motor skills. (2) How the implementation of corn seed mosaic activities can enhance fine motor skills at TK Islam Al Mansur. (3) The effectiveness of corn seed mosaic activities in improving fine motor skills of children at TK Islam Al Mansur.This research is a Classroom Action Research (CAR) conducted in two cycles. The research subjects were 20 children from Group A at TK Islam Al Mansur. The results of the study show an improvement in children's fine motor skills in each meeting during cycles I and II. In the initial stage (pre-cycle), the percentage of children who met the criteria of Developing as Expected (BSH) and Very Well Developed (BSB) was 10%. After the corn seed mosaic activity was implemented in Cycle I, the percentage increased to 40%. Following improvements made in Cycle II, the percentage rose to 87.5%. Thus, there was a total increase of 77.5%.